Development status and research recommendations for thermal extraction technology in deep hot dry rock reservoirs - Diquan Li; Ning Li; Jing Jia; Hongguang Yu; Qinghu Fan; Lichang Wang; Ahmed Mohsen (Deep Underground Science and Engineering)
Abstract Based on a comprehensive review of domestic and foreign literature, this article discusses the technical difficulties and development status of enhanced geothermal system (EGS) concerning the thermal energy extraction of deep hot dry rock (HDR) reservoirs and proposes suggestions for the research focus of numerical simulation of HDR reservoir stimulation. Additionally, it summarizes the existing methods and mainstream working fluids for HDR reservoir stimulation. The article emphasizes the significance of factors such as well location, production well depth, artificial fracture orientation, and complexity in optimizing the thermal production efficiency of the EGS. Furthermore, this article delves into a detailed discussion on the influence of fracture spacing, fracture permeability, fracture length, fluid injection rate, and injected fluid temperature on the performance of the EGS. In light of the thermo‐hydro‐mechanical coupling challenges associated with high‐temperature reservoirs, it is suggested that future research efforts should focus on investigating the impact of thermo‐induced stresses on the stability of the artificial fracture network within the EGS during long‐term (>30 years) circulation of hot and cold fluids.